Negotiating Peace with Islamists? Reviewing the Literature - Krause, Dino (Terrorism and political violence, 2025)
Armed conflicts with Islamist non-state groups appear particularly resilient against peace negotiations, while existing research on the subject remains scarce and scattered across different sub-literatures. This study provides the first systematic literature review to identify explanations for the challenges that Islamist conflicts pose for peace negotiations. Gathering theoretical arguments and empirical findings from a total of 57 studies published between 2001–2024, the analysis yields important insights. On the one hand, it shows that existing explanations focus on the Islamists’ ideology, their often cell-like internal structure and access to transnational support channels as potential barriers to negotiation onset. On the other hand, responsibility is also ascribed to governments, highlighting their tendency to overlook potentially negotiable grievances held by Islamists, the acting of external governments as veto players and the proliferation of terrorist-listings as hurdles for conflict resolution. At the same time, the reviewed studies suffer from limitations with respect to the external validity of the obtained findings. Moreover, some of the identified explanations are primarily raised in studies of transnational Islamist groups but remain largely absent from studies dealing with nationally focused Islamists. Based on the obtained findings, I propose several suggestions for future research.